Pengaruh Metode Proyek dan Praktik Langsung Terhadap Kemampuan Sains Anak Usia 5-6 Tahun di TK Buah Hati Kab. Gowa - Asrita, Asrita; Marzuki, Kartini; Amal, Azizah Amal; Zainuddin, M. Said (Jurnal Bimbingan dan Konseling Borneo, 2024)
This research is a quasi-experimental research which aims to determine the effect of the project method and direct practice on the science abilities of children aged 5-6 years at the Buah Hati Gowa Kindergarten. The independent variables in this research are project methods and direct practice, while the dependent variable is science ability. The population in this study were all students in group B Kindergarten Buah Hati District. Gowa, while the sample is group B1 as a project method experimental class with 15 students and group B2 as a direct practice method experimental class with 15 students. Data collection techniques, namely tests, observation and documentation. Meanwhile, the data analysis technique, namely descriptive statistics and infreential statistical analysis techniques with the normality test, uses the one-sample Shapiro-Wilk test with the help of SPSS 23.0 for Windows with a significance level of 0.05. The research results showed that there was an influence of the project method and direct practice on the science abilities of children aged 5-6 years in the Buah Hati Kindergarten, District. Gowa with an average score in the category of developing very well and developing according to expectations